Supplemental nicotine preloading for smoking cessation in posttraumatic stress disorder: Results from a randomized controlled trial - Dennis, Paul A. (Addict Behav, 2016)
BACKGROUND: Individuals with posttraumatic stress disorder (PTSD) are more likely to smoke and more likely to relapse following a quit attempt than individuals without PTSD. Thus, there is a significant need to study promising interventions that might improve quit rates for smokers with PTSD. One such intervention, supplemental nicotine patch-preloading, entails the use of nicotine replacement therapy prior to quitting. OBJECTIVE: The objective of this study was to conduct a randomized controlled trial of the efficacy of supplemental nicotine patch-preloading among smokers with PTSD. We hypothesized that, relative to participants in the placebo condition, participants in the nicotine patch-preloading condition would: (1) smoke less and experience reduced craving for cigarettes during the nicotine patch-preloading phase; (2) experience less smoking-associated relief from PTSD symptoms and negative affect during the preloading phase; and (3) exhibit greater latency to lapse, and higher short- and long-term abstinence rates. METHODS: Sixty-three smokers with PTSD were randomized to either nicotine or placebo patch for three weeks prior to their quit date. Ecological momentary assessment was used to assess craving, smoking, PTSD symptoms, and negative affect during the preloading period. RESULTS: Nicotine patch-preloading failed to reduce smoking or craving during the preloading phase, nor was it associated with less smoking-associated relief from PTSD symptoms and negative affect. Moreover, no differences were observed between the treatment conditions for time to lapse, 6-week abstinence, or 6-month abstinence. CONCLUSIONS: The findings from the present research suggest that supplemental nicotine patch-preloading is unlikely to substantially enhance quit rates among smokers with PTSD.